A generation of transmitter signal for 16 PSK STBC memo on FPGA based polarizone testbed / Mohd Naim Ab Kassim - Ab Kassim, Mohd Naim (2014)
This research focusing on implementation of actual experiments of FPGA board for analysis of multiple input multiple outputs (MIMO) on Space Time Block Code (STBC) scheme. Current research show that STBC is efficient to decrease the distortion effect in transmission system by provide diversity. STBC is known as a technique to transmit redundancy signal through multiple antenna and received various signal data with consistency of data transfer. In this research, Alamouti scheme will be implemented on a FPGA Testbed by Polarizone. Modulation scheme of 16 PSK with two number of transmitting antenna is implemented.